Cover Feature: A Flexible and Conductive Binder with Strong Adhesion for High Performance Silicon‐Based Lithium‐Ion Battery Anode (ChemElectroChem 9/2020). Issue 9 (3rd April 2020) - Tang, Ruixian; Ma, Lei; Zhang, Yu; Zheng, Xiao; Shi, Yongji; Zeng, Xiangyu; Wang, Xiaoyu; Wei, Liangming
Abstract : The Cover Feature shows a silicon‐based lithium‐ion battery employing a flexible and conductive binder with strong adhesion. This binder stabilizes the Si anode and effectively improves the cycling performance. More information can be found in the Article by R. Tang et al .